Going Digital, Going Global: How Digital Transformation Drives Business Model Innovation in International Firms - Adhikari, Ashish (My University, 2026)
This thesis examines how digital transformation drives business model innovation in interna-tional firms and why scaling outcomes differ across borders. The study starts from the observa-tion that digital technologies have widened the scope for new value propositions, delivery ar-rangements, and revenue models, yet understanding of these changes has remained fragmented across information systems, strategy, and international business research. A clearer explanation has therefore been needed of how digital transformation is translated into business model change and how this change is shaped by international operating conditions. The objective of the thesis is to explain the relationship between digital transformation and business model innovation in international firms and to identify the conditions under which digitally enabled business models can be transferred and scaled across borders. The thesis has been positioned at the intersection of digital transformation, business model innovation, dy-namic capabilities, and internationalisation. It has been guided by the view that digital trans-formation does not automatically produce successful business model innovation. Rather, digital opportunities are interpreted, selected, and transformed through organisational capability pro-cesses, while international outcomes are shaped by institutional and ecosystem conditions in different markets. A qualitative research design has been employed. The study has combined a systematic litera-ture review with a secondary evidence synthesis of four internationally active firms operating under different regulatory, market, and ecosystem conditions. Through this design, conceptual evidence has been integrated with case-based material to develop an explanation that is both theoretically grounded and practically relevant. The findings indicate that digital transformation has been linked to business model innovation through recurring pathways, including data-driven augmentation, digital channel reconfigura-tion, platformisation and ecosystem orchestration, and monetisation redesign. Across these pathways, business model change has been enabled by the interaction of sensing, seizing, and transforming routines. International scaling has been shaped by regulation and data governance, ecosystem complements, network position, and market readiness. A central conclusion is that business model portability and business model performance should be treated as distinct. A digitally enabled model may be transferable in technical terms, yet still perform weakly if local compliance conditions, partner structures, or market constraints are not adequately addressed. It is concluded that digital transformation should be understood not only as technological adop-tion but as a managed process of business model redesign under varying international condi-tions.
Keywords: digitalisation; business models; business; internationalisation; innovations; change; enterprises; international corporations; corporate strategies; models (objects); fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business